Experimental investigation of energy absorption of partially wrapped thin-walled aluminium-glass/epoxy tube subjected to quasi-static loading - Abbas, T. (Trans Tech Publications Ltd, 2017)
This paper describes the failure modes and energy absorption capability of partially wrapped aluminium-glass/epoxy tubes, subjected to quasi-static loading. ‎These tubes are used in aircraft and automobiles applications. Aluminium tubes were partially wrapped with 4, 6 and 8 glass/epoxy layers, using filament winding process. The 90◦ fiber orientation was used for glass/epoxy layers. Quasi-static loading of partially wrapped tubes was carried out at 5mm/min speed, using the universal ‎testing machine. The experimental results revealed that partially wrapped aluminium tubes are 42.54, 47.77 and 28.91 more ‎efficient in energy absorption as compared to the simple aluminium tubes. Furthermore, the effect of glass/epoxy layers on ‎failure modes has also been described. © 2017 Trans Tech Publications, Switzerland.